(untitled) (UNED Research Journal, 2017)
The Prusia sector of the Irazú Volcano National Park, Costa Rica, has plantations of native and exotic species, the latter includes pine, cypress and eucalyptus. I estimated the avifaunal richness with point counts (fixed-radius), in pine, eucalyptus and forest, 36 species distributed in 14 families were recorded. Eucalyptus and the forest share 90% of species. The type of habitat and the vertical species distribution were the unique two variables that showed to be associated with the type of vegetation. The low species richness found, in this study, could be explained due to altitude zone and the homogeneity of exotic vegetation patches, that could cause a decrease of resources and shelter sites, while the lack of ecological associations with the type of habitat, could be the result from edge effect, distance from the nature reserve, presence of a middle vegetation layer, or some other factors.